Copper(I)‐Catalyzed Alkylation of Aryl‐ and Alkenylsilanes Activated by Intramolecular Coordination of an Alkoxide1. Issue 48 (9th October 2013) - Tsubouchi, Akira; Muramatsu, Daisuke; Takeda, Takeshi
<x xml:space="preserve">Abstract</x> Let's coordinate: Copper(I)‐catalyzed cross‐coupling of alkenyl‐ and arylsilanes with primary alkyl iodides as well as allylic and benzylic halides as C(sp3)X electrophilic coupling partners has been realized by intramolecular activation through alkoxide coordination. This alkylation tolerates a range of functional groups including a free hydroxy group. IPr=1, 3‐bis(2, 6‐diisopropylphenyl)imidazol‐2‐ylidene.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>